Methods of testing plastics. Thermal properties. Crushing strength after heating (heat resistance) of thermosetting moulding material. Crushing strength after heating (heat resistance) of thermosetting laminated sheet or mouldings Part 1, (31st May 1978) - British Standards Institution,
No abstract available